Synthesis, molecular docking and α-glucosidase inhibition of 2-((5, 6-diphenyl-1, 2, 4-triazin-3-yl)thio)-N-arylacetamides. Issue 5 (1st March 2017) - Wang, Guangcheng; Li, Xin; Wang, Jing; Xie, Zhenzhen; Li, Luyao; Chen, Ming; Chen, Shan; Peng, Yaping
Graphical abstract: Highlights: A novel series of 2-((5, 6-diphenyl-1, 2, 4-triazin-3-yl)thio)-N-arylacetamides have been synthesized. All the synthesized compounds shown potent α-glucosidase inhibitory activity. Compound5j was found to be the most active compound. Molecular docking study was carried out to understand the ligand-enzyme interactions. Abstract: A novel series of 2-((5, 6-diphenyl-1, 2, 4-triazin-3-yl)thio)-N-arylacetamides5a –5q have been synthesized and evaluated for their α-glucosidase inhibitory activity. All newly synthesized compounds exhibited potent α-glucosidase inhibitory activity in the range of IC50  = 12.46 ± 0.13–72.68 ± 0.20 μM, when compared to the standard drug acarbose (IC50  = 817.38 ± 6.27 μM). Among the series, compound5j (12.46 ± 0.13 μM) with strong electron-withdrawing nitro group on the arylacetamide moiety was identified as the most potent inhibitor of α-glucosidase. Molecular docking study was carried out to explore the binding interactions of these compounds with α-glucosidase. Our study identifies a novel series of potent α-glucosidase inhibitors for further investigation.